Rational Designing of Ternary Cusse Electrocatalyst for Water Splitting: Layered Mastery of 2d Nanostructures - Herrera-Diaz, F; Herrera-Diaz, F (Elsevier Ltd, 2025)
The treasure hunting of effective and efficient materials for the renewable hydrogen production through the water splitting process has escalated due to the pressing demand for the clean and sustainable energy sources. In this context, the layered two-dimensional (2D) chalcogenides have become attractive options owing to their special structural and electrical characteristics. In this investigation, the 2D layered copper sulfide (CuS) and copper sulfoselenide (CuSSe) as the electrocatalysts have been carried out for the water splitting applications. The synthesis of CuS and CuSSe nanosheets was achieved by an easy and scalable solvothermal technique, permitting mastery in the fabrication of high-quality 2D layers. The successful formation of 2D layered structure was characterized by using several methods, including the X-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), and X-ray photoelectron spectroscopy (XPS). Further, the electrochemical studies of the CuS and CuSSe were conducted to investigate the water splitting performance of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The laminar 2D nanostructured ternary CuSSe electrocatalyst exhibited a smaller overpotential of −270 mV with a Tafel value of 153 mV/dec with three-fold enhancement in response rate compared to the binary sample. The results provided the crucial insights for advancing the development of efficient and sustainable materials, which could be played a key role in enabling the clean hydrogen generation and contribute significantly to the ongoing efforts to establish a hydrogen-based energy system. © 2024 Hydrogen Energy Publications LLC